A CRITICAL STUDY OF THE IMPACT OF ARAB LEADERSHIP STYLES ON ORGANISATIONAL & EMPLOYEES’ PERFORMANCE - Bualshawarib, Mariam Juma (2014)
Leaders plays vital role in ensuring high organizational performance. With an appropriate balance of motivation, ability and opportunity given to individuals; leaders promote excellent organizational performance. A fair balance of the equation including leadership style, proper work environment, adequate policies and procedures, tools to function and sufficient accountability, strong cultural values that promote transparency and provide clear guidance on desired outcome is what’s needed for employees to perform. Though studies on leadership roles in enhancing performance amongst employees are ample in developed countries, there has been a lack of research on this subject in the Middle East. Therefore, the researcher decided to evaluate Arab leadership style, organizational performance and employee performance in a country that is well known for its wealth and multi-national companies such as Dubai. Unlike many other developing countries around the GCC, Dubai seems more of a central hub that attracts people from developed and developing countries to invest or even find a career. This fact allows the researcher to have a stronger view on Arab leadership style and their impact on performance, as it comes from various nationalities and expertise in the area. The empirical research study used questionnaires with questions tailored towards determining the relationship between: Arab leadership styles and employee performance, which should indirectly determine the relationship between Arab leadership style and organizational performance. Also, the research intent was to identify the pattern of Arab leadership and the extent to which it has affected organizational performance. In addition, the researcher was interested in finding out more about potential factors responsible for low worker performance and how leadership style has affected labour management relations and productivity in four selected small scale organizations that are grouped under one holding company. After analysing the results using both qualitative and quantitative methods, it is concluded that in order to accomplish the objectives of different organisations need in Dubai, it is necessary that leaders: recognizes the needs of the workers; employs appropriate motivational tools such as right leadership style using appropriate leadership and management programs; providing workers with appropriate guidance and working tools; develop an adequate performance management system that would uncover sources of potential bias and accordingly incentives best performances.